x+7=3x+9.5

Simple and best practice solution for x+7=3x+9.5 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for x+7=3x+9.5 equation:


x+7=3x+9.5

We simplify the equation to the form, which is simple to understand
x+7=3x+9.5

We move all terms containing x to the left and all other terms to the right.
+1x-3x=+9.5-7

We simplify left and right side of the equation.
-2x=+2.5

We divide both sides of the equation by -2 to get x.
x=-1.25

See similar equations:

| (x^(2/3)y^(-(5/4)))^6 | | 1.4/7.7 | | lg(x^2-x-6)-lg(x-3)=0 | | 25x^2+35x=0 | | 5=-7+a | | 40=-8(x+2) | | 1.5y-2=y | | 1/2x+2/5=1/3x+3/4 | | 10*t+6*(0.8-t)=6 | | (x-16)2=64 | | 9x+20=2x+125 | | 4x-6=x-18 | | -5k-2+9k+6= | | 1/2(6x-4)-4x=3x-18 | | x^4+18x^2+17=0 | | 3x-x+1=2x+5 | | 7=n+5 | | x*x+25=10x | | 9n+7n-5-4= | | 4x-5y+3z= | | .75(4-8x)=0.8(5+10x)+1 | | a(3a-2)+2a(a+4)=a(a+2) | | Ln(x-15)=10 | | 4x-6-3x= | | S=4rt | | (3x^2+5)(2x^5-1)= | | 11x-20=7x+7 | | 2204.28=2(3.14(13)(13))+2(3.14(13)(h)) | | 18=5y-7 | | 48-x=4x(7) | | 5x-6x-12x= | | 2204=2(3.14(13)(13))+2(3.14(13)(h)) |

Equations solver categories